Urine Collection Method for the Diagnosis of Congenital Cytomegalovirus Infection. Issue 8 (August 2015) - Ross, Shannon A.; Ahmed, Amina; Palmer, April L.; Michaels, Marian G.; Sánchez, Pablo J.; Stewart, Audra; Bernstein, David I.; Feja, Kristina; Novak, Zdenek; Fowler, Karen B.; Boppana, Suresh B.
Abstract : Congenital cytomegalovirus infection is traditionally diagnosed by virus detection in saliva or urine. Virus culture was positive in significantly fewer urine samples collected using cotton balls in diapers (55.2%) than with samples collected by bags (93.2%) from newborns screened positive for CMV in saliva. However, polymerase chain reaction was positive in 95% of urine samples regardless of the collection method.